One summer - Baldacci, David (New York : Grand Central Pub., 2011)
Jack, terminally ill and preparing to say goodbye to his family, has a miraculous recovery after his wife is killed in a car accident and struggles to reunite his family at her childhood home on the South Carolina oceanfront.
edited hb 2015-06-16
Keywords: Life change events -- Fiction; Loss (Psychology) -- Fiction; Custody of children -- Fiction; Domestic fiction; Large type books; South Carolina -- Fiction